Microstructure and environment-dependent fatigue crack propagation properties of Ti-48Al intermetallics - Hamada, S.; Hamada, H.; Suzuki, H.; Tamin, M. N.; Nozue, A. (Kluwer Academic Publishers, 2002)
Fatigue crack propagation properties of Ti-48Al were studied by means of in-situ observation of the crack growth process under vacuum and air conditions. Three types of microstructures, namely, as-cast, duplex and fully lamellar structure were investigated in the present study. The results show that the crack growth behavior is dependent on the microstructure and the angle between the crack growth direction and orientation of lamellar colonies. The preferred path of crack propagation through the weakest phase of the structure associated with microcracking within the crack tip plastic zone has been investigated. The accelerated crack growth observed in air environment is attributed to absorption of air humidity at the crack tip plastic zone. This phenomenon is apparent through the observation of crack propagation process and the resulting fractured surface.